2016
DOI: 10.1099/ijsem.0.001173
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence that Vibrio inhibens is a heterotypic synonym of Vibrio jasicida

Abstract: Vibrio inhibens is a marine bacterium species of the genus Vibrio (Vibrionaceae, Gammaproteobacteria). The species has been shown to be closely related to members of the genus Vibrio in the so-called Harveyi clade. The clade includes at least 11 closely related species with similar physiological and biochemical properties. Due to these similarities, species of the Harveyi clade are difficult to characterize taxonomically. Previously phenotypic and genotypic properties of the V. inhibens type strain were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…The entirety of the tree, without collapsed branches, was included in the Supplementary Figure S1 . This phylogeny showed strong agreement with previous whole-genome Harveyi clade phylogenies ( Thompson et al, 2009 ; Lin et al, 2010 ; Urbanczyk et al, 2013 , 2014 , 2016 ; Ke et al, 2017 ), but unlike previous phylogenies, the aim of this phylogeny was the resolution of the non-core Harveyi subclades (e.g., V. alginolyticus, V. antiquarius, V. diabolicus , and V. parahaemolyticus ). To that end, the discovery of a well-supported V. diabolicus subclade comprised of two V. diabolicus strains (Art-Gut C1 and CNCM I-1629), two V. antiquarius strains (939 and EX25) and four V. alginolyticus strains (E0666, FF273, TS13, and V2) was novel.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The entirety of the tree, without collapsed branches, was included in the Supplementary Figure S1 . This phylogeny showed strong agreement with previous whole-genome Harveyi clade phylogenies ( Thompson et al, 2009 ; Lin et al, 2010 ; Urbanczyk et al, 2013 , 2014 , 2016 ; Ke et al, 2017 ), but unlike previous phylogenies, the aim of this phylogeny was the resolution of the non-core Harveyi subclades (e.g., V. alginolyticus, V. antiquarius, V. diabolicus , and V. parahaemolyticus ). To that end, the discovery of a well-supported V. diabolicus subclade comprised of two V. diabolicus strains (Art-Gut C1 and CNCM I-1629), two V. antiquarius strains (939 and EX25) and four V. alginolyticus strains (E0666, FF273, TS13, and V2) was novel.…”
Section: Resultssupporting
confidence: 85%
“…In contrast, these genomes shared less than 92% ANI with representative V. alginolyticus genomes, confirming that they are distinct in comparison to their nearest phylogenetic neighbor. A similar study used the 97% ANI threshold to support the conclusion that V. inhibens is a heterotypic synonym of V. jasicida ( Urbanczyk et al, 2016 ). In this study, the analysis of ANI values clearly showed that two V. antiquarius strains (939 and EX25) and four V. alginolyticus strains (E0666, FF273, TS13, and V2) are synonyms of V. diabolicus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nov. contains similarly mainly 16:0 (14-30%), 18:1 ω7c (8-24%), and summed feature 3 (35-43%) [80]. It has been proposed that V. inhibens is a later heterotypic synonym of V. jasicida [81]. The most curious fatty acid in the three isolates of the present study is the polyunsaturated 18:3 w6c (Table 3).…”
Section: Biochemical Analysis Of the Isolatesmentioning
confidence: 53%
“…This clade consists of 10 evolutionarily closely related species with validly described names (2,9). Bacteria in the clade are difficult to classify using polyphasic taxonomy and require the use of genomic data to accurately classify strains into species (9)(10)(11)(12). Studies of Harveyi clade Vibrio bacteria allow a good opportunity to compare the delineation of bacteria based on their ecology with the classification using polyphasic taxonomy.…”
mentioning
confidence: 99%